Exploring the Efficacy of Adopting English as the Medium of Instruction in Moral Education: A Study of an American Curriculum School in Sharjah, UAE - Abdelhamid A. Khalil (2025)
Moral Education (ME) is a newly added subject to all schools’ curricula in the UAE to promote tolerance and foster global principles, morals, and values shared by the overall community. Although schools are eligible to choose between English and Arabic as the language of instruction to teach ME, many schools which include mainly Arab students have opted for English as the medium of instruction (EMI) to teach ME. Therefore, the current study aims to investigate the policy of adopting EMI to teach ME at an American curriculum school in Sharjah, UAE. Moreover, eight English teachers and four members of the Senior Leadership Team were interviewed through three sets of semi-structured interviews. The study findings showed English language teachers’ disagreement with the policy. Furthermore, the findings demonstrated that teachers’ voices were fully disregarded while establishing the policy by the Senior Leadership Team.